Determination of ROS Scavenging, Antibacterial and Antifungal Potential of Methanolic Extract of Otostegia limbata (Benth.) Boiss. - Huma Mehreen Sadaf (MDPI AG, 2021)
Wide spectrum medicinal significance augments plant utilization as the primary source of significant pharmaceutical agents. In vitro investigation of antioxidant and antimicrobial activity highlights the therapeutic potential of Otostegia limbata. Methanol extract of the plant (MEP) shows considerable dose dependent antioxidant ability at six concentrations (7.81 µg/mL to 250 µg/mL) in 2.2-diphenyl-1-picrylhydrazyl (DPPH) assay, phosphomolybdate assay (PMA) and reducing power assay (RPA). The plant capability to scavenge free radicals in the mixture ranged from 37.89% to 63.50% in a concentration-dependent manner. MEP was active against five tested bacterial strains in the agar-well diffusion method. Staphylococcus aureus, gram-positive bacteria was found to be most susceptible followed by S. epidermidis with 18.80 mm and 17.47 mm mean zone of inhibition. The mean inhibition zone against gram-negative strains Klebsiella pneumonia, Pseudomonas spp. and Escherichia coli were 15.07 mm, 14.73 mm, and 12.17 mm. MEP revealed potential against Alternaria spp. and Aspergillus terreus fungal strains evaluated through agar-tube dilution assay. Aspergillus terreus was more sensitive than Alternaria spp. with an average 78.45% and 68.0% inhibition. These findings can serve as a benchmark for forthcoming scrutiny such as bioactive components discovery and drug development.